A Cognitive Linguistic Study of the Present Simple: An Experimental Study in the University of Baghdad (Journal of the College of Education for Women, 2023)
Some research reports that cognitive grammar (CG) theory has good contributions to teaching English as a foreign language. In this research, the researchers seek to apply this theory and its principles when teaching the simple present tense to Iraqi students who face difficulties in differentiating between the multiple usages of this tense. To achieve this objective, the researchers have conducted an experimental study on a group of 60 Iraqi students in the University of Baghdad, College of Education for Women. Langacker’s (2003) theory has been adopted in the analysis of the cognitive relations to understand the common and different connections of these usages of the simple present. The study has concluded that the cognitive grammar theory contributed to improving the participants' capacity in comprehending, using the present simple, and in correcting the grammatical errors that they used to commit. Moreover, the theory helped the participants to differentiate between the simple differences of English tenses when they overlap.